The Quakers in America - Hamm, Thomas D. (New York : Columbia University Press, 2003)
Provides a concise history of the Religious Society of Friends, an introduction to its beliefs and practices, and a vivid picture of the culture and controversies of the Friends today.
Meeting for worship and meeting for business -- The origins of American Quakerism, 1640-1800 -- Their separate ways : American Friends since 1800 -- Quaker faiths and practices -- Contemporary Quaker debates -- Quakers and the world -- "A quarterly meeting in herself" : Quaker women, marriage, and the family -- Quaker lives, past and contemporary.
Includes bibliographical references and index.
Print version record.
Keywords: Society of Friends -- United States; RELIGION -- Christianity -- Quaker; RELIGION -- General; Society of Friends; United States; Electronic books